INFLUENCES OF ORGANIC MANURES AND AMENDMENTS IN SOIL PHYSIOCHEMICAL PROPERTIES AND THEIR IMPACT ON GROWTH, YIELD AND NUTRIENT UPTAKE OF BANANA - K. VANILARASU; G. BALAKRISHNAMURTHY (The Bioscan, 2014)
An investigation was carried out during 2010-2011, to study the effect of organic manures (Farmyard manure, Vermicompost, Neem cake and Wood ash), organic amendments (Arbuscular mycorrhizae, Azospirillum, Phosphate Solubilising Bacteria and Trichoderma harzianum) and green manures (Sunhemp and Cowpea) in comparison with inorganic fertilizers on leaf nutrient and soil physiochemical properties of banana cv. Grand Naine. The treatment T10 with the combined application of organic manures, amendments and green manures (Farmyard manure @ 10 kg + Neem cake @ 1.25 kg + Vermicompost @ 5 kg and Wood ash @ 1.75 kg /plant + Triple green manuring with Sunhemp + Double intercropping of Cow pea + biofertilizers viz., Arbuscular Mycorrhizae @ 25 g , Azospirillum @ 50 g, Phosphate Solubilizing Bacteria @ 50 g and Trichoderma harzianum @ 50 g/plant) registered the maximum growth, yield and yield attributes, leaf nutrient status of N, P and K at 5th and 7th month after planting and soil physiochemical properties at harvesting stage because the role of organic manures and amendments to make the soil has healthy as well as possible and also, the unavailable form of soil nutrients to available form by enhancing mineralization and solubilization process in soil by adding organic manures and microbial agents make easy uptake of nutrients when crop required comparing to chemical fertilizers.